PENGGUNAAN METODE SERVQUAL UNTUK MENILAI MUTU PELAYANAN DI KLINIK PRATAMA BABUN RIZKI - br sinambela, salsabilah ramadani; Nurwati, Nurwati; Rohminatin, Rohminatin (STMIK Royal Kisaran, 2024)
Abstract: Babun Rizki Pratama Clinic is a business that operates in the health services sector. Pratama Babun Rizki Clinic is located in Haessa Air Genting Village Dusun IV, Air Batu District, Asahan Regency. The public always asks for quality medical services, but often these requests do not meet expectations, because the services provided to patients at Babunn Rizki Pratama Clinic are said to be less effective. The lack of staff at the Pratama Babun Rizki Clinic results in a long patient examination process, so that many patients receive less effective services and are at high risk of experiencing medical errors. These various problems can be overcome by using technology that carries the concept of service to patients using the Service Quality (SERVQUAL) method. The method used in this research is qualitative, where this research is carried out by distributing questionnaires to find out how respondents respond to the services provided. The results of service calculations using the Servqual method at Babun Rizki Pratama Clinic showed that 80% of respondents felt